TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE GENERAL LEDGER REPORT (Tufts Archival Research Center, 2007)
List of transactions between the Labor Management Committee (LMC) and various organizations. Gives the date of the transaction, the organization and the amount transacted.